The paradox of care: dopamine super sensitivity psychosis and catatonia following excessive antipsychotic exposure in an adolescent with first-break schizophrenia - Parikh, Parinda; Wubuli, Dilinuer; Dadem, Ananya Reddy; Gultekin, Isa; Chandra-Kaushik, Arushi; Wang, Eric; Narravula, Rithika; Chandra, Avish; Buddhavarapu, Ishant; Mendelowitz, Avigder (International Journal Of Community Medicine And Public Health, 2025)
Dopamine super sensitivity psychosis (DSP) is marked by rebound or treatment-resistant psychosis, typically linked to prolonged or poorly managed antipsychotic use. While increasingly recognized in adults, DSP in adolescents, especially with catatonia, remains underreported. The impact of fragmented psychiatric care and caregiver-driven treatment changes is rarely addressed. We describe a 13-year-old female with schizophrenia who developed severe functional decline and catatonia after years of inconsistent psychiatric management. Extensive workup, including EEG, brain MRI, and broad metabolic, infectious, autoimmune, and endocrine testing, was negative. Her history revealed frequent physician changes and abrupt medication switches without tapering, often initiated by parental concern over persistent symptoms. At presentation, she was wheelchair-bound, minimally responsive, and showed psychomotor retardation, tremors, and auditory hallucinations. Her course aligned with DSP complicated by catatonia, after incomplete or subtherapeutic trials of risperidone, olanzapine, quetiapine, aripiprazole, and cariprazine. Treatment with clozapine and high-dose lorazepam was initiated, alongside careful monitoring and structured support for the family. The patient gradually regained independence, resumed psychotherapy, and re-engaged socially, with significant improvement in psychosis. This case illustrates the rare intersection of adolescent DSP and catatonia, highlighting risks of inconsistent treatment and caregiver-driven decisions. It underscores the importance of coordinated psychiatric care, cautious medication adjustments, and comprehensive family education. Supporting caregivers emotionally and educationally is vital to improving adherence and long-term outcomes for youth with severe mental illness.